2020
DOI: 10.1111/cla.12443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring systematic biases, rooting methods and morphological evidence to unravel the evolutionary history of the genus Ficus (Moraceae)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 93 publications
0
16
1
Order By: Relevance
“…However, a recent study used genome-wide RAD loci and morphological features to infer the phylogenetic relationships in Ficus revealed that long-branch attraction led to section Pharmacosycea was the basal clade ( Rasplus et al, 2021 ). Their results also strongly support the subgenera Sycidium , Sycomorus , and Urostigma as monophyletic clades, and suggest that the polyphyletic nature of these chloroplast genome-based clades may be due to heterogeneity ( Rasplus et al, 2021 ). Thus, more research is needed to determine the reasons for nuclear and plastid discordance in figs, as it is unrealistic to rely on single genomes or small sample sizes to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study used genome-wide RAD loci and morphological features to infer the phylogenetic relationships in Ficus revealed that long-branch attraction led to section Pharmacosycea was the basal clade ( Rasplus et al, 2021 ). Their results also strongly support the subgenera Sycidium , Sycomorus , and Urostigma as monophyletic clades, and suggest that the polyphyletic nature of these chloroplast genome-based clades may be due to heterogeneity ( Rasplus et al, 2021 ). Thus, more research is needed to determine the reasons for nuclear and plastid discordance in figs, as it is unrealistic to rely on single genomes or small sample sizes to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Our placement of section Pharmacosycea ( F. maxima and F. adhatodifolia ) is consistent with previous study based on a nuclear genomic data, providing strong support that this section is sister to all other figs ( Bruun-Lund et al, 2017 ; Wang et al, 2021 ). However, a recent study used genome-wide RAD loci and morphological features to infer the phylogenetic relationships in Ficus revealed that long-branch attraction led to section Pharmacosycea was the basal clade ( Rasplus et al, 2021 ). Their results also strongly support the subgenera Sycidium , Sycomorus , and Urostigma as monophyletic clades, and suggest that the polyphyletic nature of these chloroplast genome-based clades may be due to heterogeneity ( Rasplus et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While genome-scale data can often help resolving phylogenetic relationships, they have proven frustrating when addressing difficult nodes within the Saturniidae, presumably because of the lack of signal associated with an old, rapid radiation (Hamilton et al 2021) and of the increasing probability of observing conflicting signals between markers (Kumar et al 2012). In particular, although these properties are still rarely thoroughly explored, heterogeneity in base composition and evolutionary rates of taxa and markers (e.g., Boussau et al 2014, Romiguier et al 2016, Bossert et al 2017, Borowiec et al 2019, Cruaud et al 2021, Rasplus et al 2021) as well as saturation (Borowiec 2019, Duchêne et al 2021) were identified as major causes of analytical bias in phylogenomic analyses. These factors, in concert with limited taxon sampling, may, for instance, explain the poorly resolved placement of Agliinae within the Saturniidae (Hamilton et al 2019) and constrain our understanding of the early evolutionary history of this family.…”
mentioning
confidence: 99%
“…The program is intended for fast bootstrap calculations. Three papers published in Cladistics during 2019–2020 performed analyses using MPBoot; the MPBoot results in two of those (Kallal et al., 2020; Rasplus et al., 2020) seem unremarkable, but those in the third one (Inoue et al., 2019) are unusual in that they display a relatively strong cladistic structure within a group of over 50 virtually identical specimens of Lampsilis hydiana (for which the likelihood bootstrap tree exhibited virtually no resolution). As discussed below, this may have been an artefact produced by MPBoot’s approximate algorithms, and it seems likely that proper parsimony results would have been more similar to those of maximum‐likelihood.…”
Section: Introductionmentioning
confidence: 99%